Reinforcing film, method for manufacturing device, and reinforcing method
By using acrylic-based polymer with cross-linked structures and photocuring agent in the adhesive layer of the reinforcement film, and increasing the temperature after photocuring, the existing reinforcement film has been solved with high adhesion and difficulty in peeling after surface activation treatment. The problem of high adhesion at high temperatures and good adhesion reliability are achieved.
Patent Information
- Application Number
- CN202411089614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-10
- Filing Date
- 2024-08-09
- Publication Date
- 2025-02-18
AI Technical Summary
The conventional reinforcement film has high adhesion force on the adherend after the surface activation treatment, which is difficult to peel off, and has a small adhesion force after photocuring, so the adhesion reliability is insufficient.
Using a photocurable adhesive layer containing an acrylic base polymer having a crosslinked structure, a photocuring agent and a photopolymerization initiator, the adhesive is subjected to plasma treatment before photocuring of the adhesive layer and lightly Increase the temperature after curing to enhance the bonding force.
It has achieved low adhesion on the adherent after surface activation treatment, easy peeling, and high adhesion at high temperature after photocuring, and excellent adhesion reliability.
Smart Images

Figure CN119463725A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a reinforcement film formed by fixing and laminating a film substrate and a photocurable adhesive layer. Furthermore, the present invention relates to a method for manufacturing a device having a reinforcement film attached to a surface, and a reinforcement method for fixing and laminating a reinforcement film on the surface of an adherend. Background Art
[0002] An adhesive film is sometimes attached to the surface of an optical device such as a display or an electronic device for the purpose of surface protection, impact resistance, etc. Such an adhesive film usually has an adhesive layer fixedly laminated on the main surface of a film substrate and is attached to the device surface via the adhesive layer.
[0003] By temporarily attaching an adhesive film to the surface of a device or a component of the device before use, such as during assembly, processing, or transportation of the device, damage or breakage of the adherend can be suppressed. Patent document 1 discloses a reinforcement film having a photocurable adhesive layer on a film substrate that includes an acrylic base polymer, a multifunctional (meth)acrylate as a photocuring agent, and a photopolymerization initiator.
[0004] The enhancement film has low adhesion immediately after being attached to the adherend, so it is easy to peel off from the adherend. Therefore, it can be reprocessed from the adherend, and the enhancement film can also be selectively peeled off from the position where the reinforcement of the adherend is not required. The adhesive of the enhancement film is firmly bonded to the adherend by light curing, so that the film substrate is permanently bonded to the surface of the adherend, and can be used as a reinforcement material for surface protection of devices.
[0005] Prior art literature
[0006] Patent Literature
[0007] Japanese Patent Application Publication No. 2020-132846 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Before attaching the reinforcement film to the surface of an adherend such as a device, a surface activation treatment such as a plasma treatment or a corona treatment may be performed for the purpose of cleaning the adherend surface. If the reinforcement film is attached to the surface of the adherend after the surface activation treatment, the adhesive force is higher than when the reinforcement film is attached to the adherend without the surface activation treatment, and the reinforcement film may be difficult to peel off from the adherend.
[0010] Patent Document 1 states that by making the acrylic base polymer constituting the photocurable adhesive contain no nitrogen atoms, the adhesive strength to the adherend is low even when the adherend surface is activated, the reinforcing film can be easily peeled off, and the adhesive strength is increased when the adhesive is photocured. However, the adhesive strength of the adhesive after photocuring of the reinforcing film in Patent Document 1 is low at high temperatures, and the bonding reliability is insufficient.
[0011] Solutions for solving problems
[0012] In view of the above problems, an object of the present invention is to provide a reinforcing film which has low adhesion to an adherend before the adhesive is photocured and is easy to peel off, even when the adherend surface is activated by plasma or the like, and has high adhesion at high temperature after the adhesive is photocured and excellent bonding reliability.
[0013] The reinforcement film of the present invention comprises an adhesive layer fixedly laminated on one main surface of a film substrate. The adhesive layer is formed of a photocurable composition containing an acrylic base polymer having a crosslinked structure, a photocuring agent, and a photopolymerization initiator.
[0014] The acrylic base polymer contains one or more monomers selected from the group consisting of hydroxyl group-containing monomers and carboxyl group-containing monomers and a nitrogen atom-containing monomer as monomer components. The content of the nitrogen atom-containing monomer is preferably 0.3 to 10 parts by weight based on 100 parts by weight of the total monomer component of the acrylic base polymer.
[0015] The acrylic base polymer preferably has a crosslinking structure introduced by using 0.05 to 1.0 parts by weight of a crosslinking agent based on 100 parts by weight of the polymer. Examples of the crosslinking agent include isocyanate crosslinking agents and epoxy crosslinking agents.
[0016] The photocurable composition constituting the adhesive layer comprises a multifunctional (meth)acrylate having an oxyalkylene chain but not having a carbamate bond and a carbamate (meth)acrylate as a photocuring agent. The amount of the multifunctional (meth)acrylate having an oxyalkylene chain but not having a carbamate bond is preferably 3 to 30 parts by weight relative to 100 parts by weight of the acrylic base polymer. The amount of the carbamate (meth)acrylate is preferably 0.03 to 5 parts by weight relative to 100 parts by weight of the acrylic base polymer.
[0017] The functional group equivalent of the (meth)acryloyl group of the multifunctional (meth)acrylate having an oxyalkylene chain but not having a urethane bond may be 80 to 500 g / eq. The functional group equivalent of the (meth)acryloyl group of the urethane (meth)acrylate may be 80 to 5000 g / eq. The urethane (meth)acrylate may have 4 or more (meth)acryloyl groups in one molecule.
[0018] The adhesive force F0 of the adhesive layer to the polyimide film at 25°C before photocuring is preferably 0.4 N / 25 mm or less, and the adhesive force F1 to the plasma-treated polyimide film at 25°C is 1.4 times or less of F0. F1 is preferably 0.5 N / 25 mm or less.
[0019] The adhesive force F2 of the adhesive layer to the plasma-treated polyimide film after photocuring at 25°C is 3.0 N / 25 mm or more, and the adhesive force F3 at 85°C is 1.0 N / 25 mm or more. The shear storage modulus of the adhesive layer after photocuring at 25°C is preferably 150 kPa or less.
[0020] After the surface of the device as the adherend is attached with the above-mentioned enhancement film and temporarily fixed, the adhesive layer is photocured to obtain a device with an enhancement film. The device can be a flexible device that can be bent, and the adherend (enhancement object) of the enhancement film can be a bendable image display element. The adherend can also include a polyimide film.
[0021] Before temporarily fixing the reinforcement film, the surface of the adherend may be subjected to activation treatment such as plasma treatment. Alternatively, after temporarily fixing the reinforcement film to the adherend and before photocuring the adhesive layer, the reinforcement film temporarily fixed to the adherend may be cut off to remove the reinforcement film from a portion of the adherend (non-reinforcement target area).
[0022] Effects of the Invention
[0023] The adhesive layer of the reinforcement film of the present invention is formed of a photocurable composition. By photocuring the adhesive layer after bonding to the adherend, the adhesive strength to the adherend is increased. The adhesive layer has low adhesive strength to the adherend subjected to surface activation treatment before photocuring, and is easily peeled from the adherend. The adhesive after photocuring has high adhesive strength even at high temperatures and has excellent bonding reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a cross-sectional view showing the stacked structure of the reinforcement film.
[0025] Figure 2 It is a cross-sectional view showing the stacked structure of the reinforcement film.
[0026] Figure 3 It is a cross-sectional view showing a device to which a reinforcing film is attached.
[0027] Description of Reference Numerals
[0028] 1: film substrate; 2: adhesive layer; 10: reinforcing film; 5: release liner; 20: adherend. DETAILED DESCRIPTION
[0029] Figure 1 1 is a cross-sectional view showing an embodiment of a reinforcement film. The reinforcement film 10 includes an adhesive layer 2 on one main surface of a film substrate 1. The adhesive layer 2 is fixedly laminated on one main surface of the film substrate 1. The adhesive layer 2 is a photocurable adhesive formed of a photocurable composition, and is cured by irradiation with active light such as ultraviolet rays, thereby increasing the adhesive strength with the adherend.
[0030] Figure 2 It is a cross-sectional view of a reinforcing film in which a release liner 5 is temporarily fixed to the main surface of the pressure-sensitive adhesive layer 2 . Figure 3 It is a cross-sectional view showing a state where the reinforcing film 10 is attached to the surface of the device 20 .
[0031] The release liner 5 is peeled off from the surface of the adhesive layer 2, and the exposed surface of the adhesive layer 2 is attached to the surface of the device 20, thereby attaching the reinforcement film 10 to the surface of the device 20. In this state, the adhesive layer 2 is before photocuring, and is in a state where the reinforcement film 10 (adhesive layer 2) is temporarily fixed to the device 20. By photocuring the adhesive layer 2, the adhesive force at the interface between the device 20 and the adhesive layer 2 increases, and the device 20 and the reinforcement film 10 are fixed.
[0032] “Anchored” means that two stacked layers are firmly bonded and peeling at the interface between them is impossible or difficult. “Temporary anchored” means that the adhesive force between two stacked layers is weak and peeling at the interface between them is easy.
[0033] Figure 2 In the reinforcement film shown, the film substrate 1 is fixed to the adhesive layer 2, and the release liner 5 is temporarily fixed to the adhesive layer 2. When the film substrate 1 and the release liner 5 are peeled off, peeling occurs at the interface between the adhesive layer 2 and the release liner 5, and the adhesive layer 2 is maintained fixed to the film substrate 1. No adhesive remains on the release liner 5 after peeling.
[0034] Figure 3 In the device with the reinforcement film 10 attached, the device 20 and the adhesive layer 2 are temporarily fixed before the photocuring of the adhesive layer 2. When the film substrate 1 is peeled off from the device 20, peeling occurs at the interface between the adhesive layer 2 and the device 20, and the adhesive layer 2 is kept fixed to the film substrate 1. Since no adhesive remains on the device 20, it is easy to reprocess. After the adhesive layer 2 is photocured, the adhesive force between the adhesive layer 2 and the device 20 increases, so it is difficult to peel the reinforcement film 10 from the device 20. When the two are peeled off, the cohesive failure of the adhesive layer 2 sometimes occurs.
[0035] [Constitution of the reinforcement film]
[0036] <Film base material>
[0037] A plastic film is used as the film substrate 1. In order to fix the film substrate 1 and the adhesive layer 2, it is preferred that the surface of the film substrate 1 on which the adhesive layer 2 is to be attached is not subjected to a release treatment.
[0038] The thickness of the film substrate 1 is, for example, about 4 to 500 μm. From the viewpoint of strengthening the device by imparting rigidity, mitigating impact, etc., the thickness of the film substrate 1 is preferably 12 μm or more, more preferably 30 μm or more, and further preferably 45 μm or more. From the viewpoint of making the reinforcing film flexible and improving operability, the thickness of the film substrate 1 is preferably 300 μm or less, more preferably 200 μm or less. In order to make the reinforcing film flexible and foldable, the thickness of the film substrate 1 is preferably 125 μm or less, more preferably 100 μm or less. From the viewpoint of taking into account both mechanical strength and flexibility, the compressive strength of the film substrate 1 is preferably 100 to 3000 kg / cm 2 , more preferably 200 to 2900 kg / cm 2 , more preferably 300 to 2800 kg / cm 2 , particularly preferably 400 to 2700 kg / cm 2 .
[0039] As the plastic material constituting the film substrate 1, polyester resins, polyolefin resins, cyclic polyolefin resins, polyamide resins, polyimide resins, polyetheretherketone resins, etc. can be cited. In the enhanced film for optical devices such as displays, the film substrate 1 is preferably a transparent film. In addition, in the case where the adhesive layer 2 is photocured by irradiating active light from the film substrate 1 side, the film substrate 1 preferably has transparency for the active light used in the curing of the adhesive layer. Considering both mechanical strength and transparency, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate are preferably used. In the case where the adhesive layer is cured by irradiating active light from the adherend side, as long as the adherend has transparency to the active light, the film substrate 1 may also be opaque to the active light.
[0040] Functional coatings such as an easy-adhesion layer, an easy-slip layer, a release layer, an antistatic layer, a hard coating layer, and an antireflection layer may be provided on the surface of the film substrate 1. It should be noted that, as described above, in order to fix the film substrate 1 and the adhesive layer 2, it is preferred that a release layer is not provided on the surface of the film substrate 1 to which the adhesive layer 2 is attached.
[0041] <Adhesive layer>
[0042] The adhesive layer 2 fixedly laminated on the film substrate 1 is formed of a photocurable composition comprising a base polymer, a photocuring agent, and a photopolymerization initiator. The adhesive layer 2 has a small adhesive force to adherends such as devices and device components before photocuring, so it is easy to peel off. The adhesive layer 2 has an improved adhesive force to the adherend by photocuring, so even when the device is used, the reinforcing film is not easy to peel off from the device surface, and the bonding reliability is excellent.
[0043] Photocurable adhesives hardly cure under normal storage conditions, but cure by irradiation with active light such as ultraviolet rays. Therefore, the reinforcing film of the present invention has the advantages of being able to arbitrarily set the curing timing of the adhesive layer 2 and being able to flexibly cope with the lead time of the process.
[0044] The thickness of the adhesive layer 2 is, for example, about 1 to 300 μm. There is a tendency that the greater the thickness of the adhesive layer 2, the higher the adhesion to the adherend. On the other hand, when the thickness of the adhesive layer 2 is too large, the fluidity before photocuring is sometimes high, and handling becomes difficult. Therefore, the thickness of the adhesive layer 2 is preferably 3 to 100 μm, more preferably 5 to 50 μm, further preferably 6 to 40 μm, and particularly preferably 8 to 30 μm. From the viewpoint of thinning, the thickness of the adhesive layer 2 can be less than 25 μm, less than 20 μm, or less than 18 μm.
[0045] When the reinforcing film is used in an optical device such as a display, the total light transmittance of the adhesive layer 2 is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. The haze of the adhesive layer 2 is preferably 2% or less, more preferably 1% or less, further preferably 0.7% or less, and particularly preferably 0.5% or less.
[0046] Hereinafter, preferred embodiments of the respective components of the photocurable composition constituting the pressure-sensitive adhesive layer 2 will be described in order.
[0047] (Base polymer)
[0048] The base polymer is the main constituent of the adhesive composition and is the main factor that determines the adhesive strength of the adhesive layer. The adhesive composition contains an acrylic polymer as the base polymer. Preferably, more than 50% by weight of the adhesive composition is an acrylic polymer. The acrylic base polymer has excellent optical transparency and adhesion, and the adhesive strength is easy to control.
[0049] As the acrylic polymer, it is preferable to use an acrylic polymer containing an alkyl (meth)acrylate as a main monomer component. In addition, in this specification, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0050] As the alkyl (meth)acrylate, preferably one having an alkyl group with carbon atoms of 1 to 20. The alkyl (meth)acrylate may have a branched alkyl group or a cyclic alkyl group (alicyclic alkyl group).
[0051] Specific examples of the (meth)acrylic acid alkyl ester having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylate. isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like.
[0052] Specific examples of the alkyl (meth)acrylate having an alicyclic alkyl group include: cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate and the like; (meth)acrylate having a dicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; (meth)acrylate having a tricyclic or higher aliphatic hydrocarbon ring such as tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate. The alkyl (meth)acrylate having an alicyclic alkyl group may be an alkyl (meth)acrylate having a substituent on the ring such as 3,3,5-trimethylcyclohexyl (meth)acrylate. Furthermore, the (meth)acrylate alkyl ester having an alicyclic alkyl group may be a (meth)acrylate having a condensed ring of an alicyclic structure and a ring structure having an unsaturated bond, such as dicyclopentenyl (meth)acrylate.
[0053] The content of the alkyl (meth)acrylate is preferably 50 parts by weight or more, more preferably 60 parts by weight or more, and may be 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, or 95 parts by weight or more, relative to 100 parts by weight of the total amount of monomer components constituting the polymer.
[0054] From the viewpoint of lowering the glass transition temperature (Tg) of the acrylic base polymer and improving the adhesive strength in a wide temperature range, the alkyl group of the (meth)acrylic acid alkyl ester is preferably a chain alkyl group. The chain alkyl group may be linear or branched.
[0055] Among the exemplified alkyl (meth)acrylates, those having an alkyl group with 1 to 9 carbon atoms are preferred from the viewpoint of lowering the Tg of the base polymer. 1-9 Alkyl ester. The glass transition temperature of the homopolymer of the (meth)acrylic acid alkyl ester is preferably -50°C or lower, and among them, the (meth)acrylic acid C ester having an alkyl group with 6 to 9 carbon atoms is preferred. 6-9 Alkyl esters.
[0056] (Meth)acrylic acid C having a glass transition temperature of -50°C or less as a homopolymer 6-9 Specific examples of the alkyl ester include 2-ethylhexyl acrylate (Tg: -70°C), n-hexyl acrylate (Tg: -65°C), n-octyl acrylate (Tg: -65°C), isononyl acrylate (Tg: -60°C), n-nonyl acrylate (Tg: -58°C), isooctyl acrylate (Tg: -58°C), etc. Among these, 2-ethylhexyl acrylate and n-octyl acrylate are preferred because they have low Tg and can reduce the storage elastic modulus of the adhesive.
[0057] The acrylic base polymer preferably has the largest content of (meth)acrylic acid (main monomer) in the monomers constituting the acrylic base polymer. 6-9 Alkyl ester. Relative to 100 parts by weight of the total amount of the monomer components constituting the polymer, (meth)acrylic acid C 6-9 The amount of the alkyl ester is preferably 40 parts by weight or more, more preferably 50 parts by weight or more, and may be 55 parts by weight or more, 60 parts by weight or more, or 65 parts by weight or more.
[0058] The acrylic base polymer may contain two or more (meth)acrylic acid alkyl esters as monomer components, and may contain (meth)acrylic acid C 1-9 Alkyl esters and (meth) acrylic acid C 10-20 The homopolymer of the (meth)acrylic acid alkyl ester having a long-chain alkyl group with 10 or more carbon atoms has a temperature range (plateau region) in which the temperature dependence of viscoelasticity is small at a temperature higher than Tg. 10-20The alkyl ester as a monomer component reduces the temperature dependence of the storage elastic modulus, and may suppress warping of the adherend accompanying temperature changes and peeling of the reinforcement film from the adherend.
[0059] Since the temperature range of the plateau region is wide and the storage elastic modulus in the plateau region is small, the (meth) acrylic acid C 10-20 Among the chain alkyl esters, (meth)acrylic acid C 12-18 Among them, lauryl (meth)acrylate and isostearyl (meth)acrylate are preferred, and lauryl acrylate (lauryl acrylate) is particularly preferred.
[0060] The acrylic base polymer contains (meth)acrylic acid C 10-20 When the alkyl ester is used as the monomer component, the (meth)acrylic acid C 10-20 The amount of the alkyl ester is preferably 1 to 40 parts by weight, more preferably 2 to 30 parts by weight, further preferably 3 to 25 parts by weight, and may be 4 to 20 parts by weight or 5 to 15 parts by weight.
[0061] In addition to containing (meth) alkyl acrylate, acrylic acid base polymer also contains hydroxyl-containing monomer and / or carboxyl-containing monomer as a constituent monomer component. The hydroxyl and carboxyl groups of the base polymer become reaction points with the cross-linking agent described later. For example, when using an isocyanate cross-linking agent, as a monomer component of the base polymer, it is preferred to contain a hydroxyl-containing monomer. When using an epoxy cross-linking agent, as a monomer component of the base polymer, it is preferred to contain a carboxyl-containing monomer. By introducing a cross-linked structure in the base polymer, there is a tendency that the cohesive force is improved and the peelability of the adhesive layer 2 before photocuring from the adherend is improved.
[0062] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and 4-(hydroxymethyl)cyclohexylmethyl (meth)acrylate. Among these, 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate are preferred because they contribute greatly to improving the adhesive strength of the adhesive after photocuring.
[0063] Examples of carboxyl group-containing monomers include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among them, acrylic acid and methacrylic acid are preferred, and acrylic acid is particularly preferred, from the perspective of increasing the cohesiveness of the adhesive and thus easily improving the adhesive force and adhesive retention.
[0064] From the viewpoint of appropriately introducing a cross-linked structure formed by a cross-linking agent such as an isocyanate cross-linking agent or an epoxy cross-linking agent, the total amount of the hydroxyl group-containing monomer and the carboxyl group-containing monomer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may also be 0.7 parts by weight or more or 1.0 parts by weight or more, relative to 100 parts by weight of the total amount of the constituent monomer components of the acrylic base polymer.
[0065] Since hydroxyl and carboxyl groups are highly polar, when the amount of hydroxyl-containing monomers and carboxyl-containing monomers in the monomer components constituting the acrylic base polymer is large, there is a tendency that the cohesive force of the polymer becomes high and the storage elastic modulus of the adhesive layer after photocuring becomes large. From the viewpoint of reducing the storage elastic modulus of the adhesive layer 2, the total amount of hydroxyl-containing monomers and carboxyl-containing monomers is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, further preferably 10 parts by weight or less, and may also be 7 parts by weight or less or 5 parts by weight or less, relative to 100 parts by weight of the total amount of the monomer components constituting the acrylic base polymer.
[0066] The acrylic base polymer contains a nitrogen atom-containing monomer as a constituent monomer component. The nitrogen atom-containing monomer has high polarity, high cohesive force, and a high glass transition temperature of the homopolymer. Therefore, by making the acrylic base polymer contain a nitrogen atom-containing monomer as a monomer component, there is a tendency for the adhesive force of the adhesive layer after photocuring to be improved at a high temperature.
[0067] Examples of nitrogen atom-containing monomers include N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N-acryloylmorpholine, N-vinylcarboxylic acid amides, and N-vinylcaprolactam. Among them, N-vinylpyrrolidone is particularly preferred because of its high cohesive force and its large contribution to improving the adhesive force at high temperatures.
[0068] From the viewpoint of improving the adhesive force of the adhesive layer after photocuring at high temperature, the amount of the nitrogen atom-containing monomer is preferably 0.3 parts by weight or more, more preferably 0.5 parts by weight or more, and may be 0.7 parts by weight or more relative to 100 parts by weight of the total amount of the monomer components constituting the polymer. Even a small amount of the nitrogen atom-containing monomer can contribute to improving the adhesive force at high temperature.
[0069] When the amount of nitrogen-atom-containing monomers in the monomer components of the acrylic base polymer is large, there is a tendency that the cohesive force of the base polymer is high and the glass transition temperature of the adhesive layer becomes high, and there is a tendency that the storage elastic modulus of the adhesive layer after photocuring becomes large. In addition, when the amount of nitrogen-atom-containing monomers is large, there is a tendency that the adhesive force of the adhesive layer 2 before photocuring is high and the peeling of the reinforcing film from the adherend becomes difficult, especially for adherends subjected to surface activation treatments such as plasma treatment, this tendency is significant. From the viewpoint of reducing the adhesive force of the adhesive before photocuring and reducing the storage elastic modulus of the adhesive after photocuring, the amount of nitrogen-atom-containing monomers is preferably 10 parts by weight or less, more preferably 7 parts by weight or less, and may also be 5 parts by weight or less or 3 parts by weight or less, relative to 100 parts by weight of the total amount of the monomer components of the acrylic base polymer.
[0070] The acrylic base polymer may contain monomer components other than those described above. The acrylic base polymer may contain, for example, vinyl ester monomers, aromatic vinyl monomers, epoxy group-containing monomers, vinyl ether monomers, sulfone group-containing monomers, phosphoric acid group-containing monomers, acid anhydride group-containing monomers, etc. as monomer components.
[0071] From the viewpoint of providing the adhesive with excellent adhesiveness, the glass transition temperature of the acrylic base polymer is preferably -30°C or lower, more preferably -40°C or lower, further preferably -50°C or lower, and may be -55°C or lower or -60°C or lower. The glass transition temperature of the acrylic base polymer is usually -100°C or higher, and may be -80°C or higher or -70°C or higher.
[0072] The glass transition temperature (Tg) is the temperature (peak temperature) at which the loss tangent tanδ in the viscoelasticity measurement reaches a maximum. The theoretical glass transition temperature can also be used instead of the glass transition temperature based on the viscoelasticity measurement. The theoretical Tg is the glass transition temperature Tg of the homopolymer of the monomer component constituting the polymer. i and the weight fraction W of each monomer component i It is calculated by the following Fox formula.
[0073] 1 / Tg=Σ(W i / Tg i )
[0074] Tg is the theoretical glass transition temperature of the polymer (unit: K), W i is the weight fraction of monomer component i (copolymerization ratio based on weight), Tg iis the glass transition temperature of the homopolymer of monomer component i (unit: K). As the glass transition temperature of the homopolymer, the value described in the third edition of Polymer Handbook (John Wiley & Sons, Inc., 1989) can be used. The glass transition temperature of the homopolymer of a monomer not described in the above literature can be the peak temperature of tan δ measured based on dynamic viscoelasticity.
[0075] The above-mentioned monomer components are polymerized by various known methods such as solution polymerization, emulsion polymerization, and bulk polymerization to obtain an acrylic polymer as a base polymer. From the perspective of the balance of characteristics such as the adhesion and holding power of the adhesive, and the cost, solution polymerization is preferred. As a solvent for solution polymerization, ethyl acetate, toluene, etc. can be used. The solution concentration is usually about 20 to 80% by weight. As a polymerization initiator used in solution polymerization, various known polymerization initiators such as azo and peroxide can be used. In order to adjust the molecular weight, a chain transfer agent can be used. The reaction temperature is usually about 50 to 80°C, and the reaction time is usually about 1 to 8 hours.
[0076] The weight average molecular weight of the acrylic base polymer is preferably 200,000 or more, more preferably 300,000 or more, and further preferably 500,000 or more. The larger the weight average molecular weight of the base polymer, the more there is a tendency for the adhesive force at high temperature to be improved. From the viewpoint of improving the adhesive force at high temperature, the weight average molecular weight of the acrylic base polymer is preferably 1,000,000 or more, more preferably 1,300,000 or more, and may also be 1,500,000 or more, 1,600,000 or more, or 1,700,000 or more.
[0077] When the weight average molecular weight of the base polymer is too large, there is a tendency that the storage elastic modulus of the adhesive is large, and the bonding force and flexibility are reduced. Therefore, the weight average molecular weight of the acrylic base polymer is preferably less than 3,000,000, more preferably less than 2,500,000, and may be less than 2,200,000 or less than 2,000,000. When a cross-linked structure is introduced into the base polymer, the molecular weight of the base polymer refers to the molecular weight before the cross-linked structure is introduced.
[0078] (Crosslinking agent)
[0079] From the viewpoint of making the adhesive have appropriate cohesive force, showing bonding force and ensuring the peelability of the adhesive layer before photocuring from the adherend, it is preferred to introduce a crosslinked structure in the base polymer. For example, a crosslinking agent is added to the solution after the base polymer is polymerized, and heating is performed as required to thereby introduce a crosslinked structure. The crosslinking agent has more than 2 crosslinking functional groups in one molecule. The crosslinking agent can have more than 3 crosslinking functional groups in one molecule.
[0080] As the crosslinking agent, isocyanate crosslinking agents, epoxy crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, carbodiimide crosslinking agents, metal chelate crosslinking agents, etc. can be cited. These crosslinking agents react with functional groups such as hydroxyl groups and carboxyl groups introduced into the acrylic base polymer to form a crosslinked structure. From the perspective of high reactivity with hydroxyl groups and carboxyl groups of the acrylic base polymer and easy introduction of a crosslinked structure, isocyanate crosslinking agents and epoxy crosslinking agents are preferred.
[0081] As the isocyanate-based crosslinking agent, a polyisocyanate having two or more isocyanate groups in one molecule is used. The isocyanate-based crosslinking agent may have three or more isocyanate groups in one molecule. Examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / toluene diisocyanate trimer adducts (e.g., "TAKENATE D101E" manufactured by Mitsui Chemicals), trimethylolpropane / hexamethylene diisocyanate trimer adducts (e.g., "CORONATE HL" manufactured by Tosoh), trimethylolpropane adducts of xylylene diisocyanate (e.g., "TAKENATE D110N" manufactured by Mitsui Chemicals), isocyanurates of hexamethylene diisocyanate (e.g., "CORONATE 300" manufactured by Tosoh), and isocyanurates of hexamethylene diisocyanate (e.g., "CORONATE 500" manufactured by Tosoh). As the isocyanate crosslinking agent, an isocyanate compound having a biuret group (for example, "DURANATE 24A-100" manufactured by Asahi Chemical Industry Co., Ltd.) or an isocyanate compound having an allophanate group can be used.
[0082] As the epoxy crosslinking agent, a multifunctional epoxy compound having two or more epoxy groups in one molecule can be used. The epoxy crosslinking agent can have three or more or four or more epoxy groups in one molecule. The epoxy group of the epoxy crosslinking agent can be a glycidyl group. Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. As the epoxy crosslinking agent, commercially available products such as "Denacol" manufactured by Nagase ChemteX, and "TETRAD X" and "TETRAD C" manufactured by Mitsubishi Gas Chemical can be used.
[0083] The amount of crosslinking agent used can be appropriately adjusted according to the composition and molecular weight of the acrylic base polymer, and is preferably about 0.01 to 3 parts by weight relative to 100 parts by weight of the acrylic base polymer. The more the amount of crosslinking agent, the higher the crosslinking density of the base polymer, the greater the storage elastic modulus, and the tendency of the residual glue on the adherend to be suppressed when the reinforcing film is peeled off from the adherend. On the other hand, when the amount of crosslinking agent is too much, there is a tendency for the adhesive force of the adhesive layer after photocuring to decrease, especially the adhesive force at high temperature to become smaller. From the perspective of taking into account the low adhesive force (light peelability) of the adhesive layer before photocuring and the high adhesive force of the adhesive layer after photocuring, the amount of crosslinking agent is more preferably 0.05 to 1.0 parts by weight, more preferably 0.1 to 0.7 parts by weight, and can also be 0.15 to 0.6 parts by weight, 0.2 to 0.5 parts by weight or 0.25 to 0.4 parts by weight.
[0084] (Light curing agent)
[0085] The adhesive composition constituting the adhesive layer 2 contains, in addition to the base polymer, a compound having two or more photopolymerizable functional groups in one molecule as a photocuring agent. The adhesive composition containing the photocuring agent has photocurability, and when the adhesive composition is attached to an adherend and then photocured, the adhesive strength to the adherend is improved.
[0086] From the viewpoint of compatibility with the base polymer, the photocuring agent is preferably liquid at room temperature. The photopolymerizable functional group of the photocuring agent preferably has polymerizability based on photoradical reaction. As the photocuring agent, a compound having two or more ethylenically unsaturated bonds in one molecule is preferred, and from the viewpoint of showing appropriate compatibility with the acrylic base polymer, a multifunctional (meth) acrylate is preferred.
[0087] In the present invention, as a photocuring agent, a multifunctional (meth) acrylate without a carbamate bond and a multifunctional (meth) acrylate with a carbamate bond are used. That is, the photocurable composition constituting the adhesive layer 2 contains a multifunctional (meth) acrylate without a carbamate bond and a multifunctional (meth) acrylate with a carbamate bond. Hereinafter, the multifunctional (meth) acrylate with a carbamate bond is described as "carbamate (meth) acrylate". In addition, sometimes the multifunctional (meth) acrylate without a carbamate bond is abbreviated as "multifunctional (meth) acrylate".
[0088] The polyfunctional (meth)acrylate without a urethane bond preferably has an oxyalkylene chain. As described later, the polyfunctional (meth)acrylate with an oxyalkylene chain has lower compatibility with the acrylic base polymer than the polyfunctional (meth)acrylate without an oxyalkylene chain, and there is a tendency that the initial adhesion of the adhesive layer becomes smaller due to the formation of WBL.
[0089] As the polyfunctional (meth)acrylate having an oxyalkylene chain, compounds having (meth)acryloyl groups at both ends of the polyoxyalkylene chain such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate can be cited (polyalkylene glycol di(meth)acrylate). The polyfunctional (meth)acrylate having an oxyalkylene chain can be an ester of a polyol modified with oxyalkylene and (meth)acrylic acid. As the ester of a polyol modified with oxyalkylene and (meth)acrylic acid, bisphenol A oxyalkylene-modified di(meth)acrylate, isocyanuric acid oxyalkylene-modified tri(meth)acrylate, trimethylolpropane oxyalkylene-modified tri(meth)acrylate, pentaerythritol oxyalkylene-modified di(meth)acrylate, pentaerythritol oxyalkylene-modified tri(meth)acrylate, dipentaerythritol oxyalkylene-modified poly(meth)acrylate, and the like can be cited.
[0090] In the polyfunctional (meth)acrylate containing an oxyalkylene chain, as the oxyalkylene group, a (poly)oxyethylene group or a (poly)oxypropylene group is preferred, and a (poly)oxyethylene group is particularly preferred. The chain length n of the oxyalkylene group (the number of repeating units of the oxyalkylene group) is about 1 to 15. When a plurality of oxyalkylene chains are contained in one molecule, the preferred average chain length n is 1 to 15. The (average) chain length n of the oxyalkylene chain can be 12 or less, 10 or less, 8 or less, 6 or less, 5 or less, 4 or less, or 3 or less. By adjusting the type and chain length of the oxyalkylene group, the compatibility with the acrylic base polymer can be adjusted.
[0091] As the photocuring agent, two or more multifunctional (meth)acrylates without urethane bonds may be used in combination. For example, a multifunctional (meth)acrylate having relatively low compatibility with the acrylic base polymer and a multifunctional (meth)acrylate having relatively high compatibility with the acrylic base polymer may be used in combination. For example, a multifunctional (meth)acrylate without an oxyalkylene chain has high compatibility with the acrylic base polymer compared to a multifunctional (meth)acrylate having an oxyalkylene chain.
[0092] Examples of the polyfunctional (meth)acrylate not having an oxyalkylene chain include esters of polyols and (meth)acrylic acid such as bisphenol A di(meth)acrylate, alkanediol di(meth)acrylate, glycerol di(meth)acrylate, glycerol tri(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, isocyanurate tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol poly(meth)acrylate; and epoxy (meth)acrylates.
[0093] From the viewpoint of compatibility with the acrylic base polymer, the molecular weight of the multifunctional (meth)acrylate as a photocuring agent is preferably 1500 or less, more preferably 1000 or less, and may be 800 or less, 500 or less, or 400 or less. From the viewpoint of achieving both compatibility with the acrylic base polymer and improved adhesive force after photocuring, the functional group equivalent (g / eq) of the multifunctional (meth)acrylate is preferably 500 or less, more preferably 400 or less, further preferably 300 or less, particularly preferably 200 or less, and may be 180 or less or 160 or less.
[0094] On the other hand, if the functional group equivalent of the multifunctional (meth)acrylate is too small, the crosslinking point density of the adhesive layer after photocuring becomes high, and sometimes the adhesion is reduced. Therefore, the functional group equivalent of the multifunctional (meth)acrylate is preferably 80 or more, more preferably 100 or more, and may be 120 or more or 130 or more.
[0095] By including a multifunctional (meth)acrylate having an oxyalkylene chain and a urethane (meth)acrylate as a photocuring agent, there is a tendency that the adhesive force (initial adhesive force) of the adhesive layer before photocuring becomes smaller, and there is a tendency that the increase in the initial adhesive force is suppressed even for an adherend subjected to a surface activation treatment such as a plasma treatment. In addition, by including a urethane (meth)acrylate as a photocuring agent, there is a tendency that the adhesive force of the adhesive layer after photocuring, especially the adhesive force at a high temperature, becomes larger.
[0096] Urethane (meth) acrylate is a compound having one or more urethane bonds and two or more (meth) acryloyl groups in one molecule, preferably containing two or more urethane bonds in one molecule. Urethane (meth) acrylate having two or more urethane bonds is obtained, for example, by the reaction of a polyisocyanate with a (meth) acrylic compound having a hydroxyl group, and the isocyanate group of the polyisocyanate is bonded to the hydroxyl group of the (meth) acrylic compound to form a urethane bond.
[0097] The polyisocyanate may be any one of an aromatic polyisocyanate, an alicyclic polyisocyanate and an alicyclic polyisocyanate. Among them, aromatic polyisocyanates and aliphatic polyisocyanates are preferred. As the aromatic polyisocyanate, toluene diisocyanate (TDI) is particularly preferred. Toluene diisocyanate may be any one of 2,4-toluene diisocyanate and 2,6-toluene diisocyanate, or a mixture of the two. As the aliphatic polyisocyanate, hexamethylene diisocyanate (HDI) is particularly preferred.
[0098] The polyisocyanate may be a trifunctional isocyanate having a cyanuric acid skeleton. Examples of the trifunctional isocyanate having a cyanuric acid skeleton include TDI trimer and HDI trimer. The polyisocyanate may also be a polyisocyanate having a biuret group or an allophanate group.
[0099] The polyisocyanate may be an isocyanate-terminated urethane prepolymer obtained by reacting a polyol with a polyisocyanate. The isocyanate-terminated urethane prepolymer may be a high molecular weight product obtained by reacting a high molecular weight polyol such as polyester polyol, polycarbonate polyol, or polyether polyol with a polyisocyanate.
[0100] Examples of the (meth)acrylic compound having a hydroxyl group include compounds having one hydroxyl group and one (meth)acryloyl group, such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxymethacrylamide, and hydroxyethylacrylamide; and compounds having one hydroxyl group and two or more (meth)acryloyl groups, such as pentaerythritol tri(meth)acrylate, dipentaerythritol penta(meth)acrylate, trimethylolpropane di(meth)acrylate, and isocyanuric acid di(meth)acrylate.
[0101] Among them, the (meth)acrylic compound having a hydroxyl group is preferably a compound having one hydroxyl group and two or more (meth)acryloyl groups, and specific examples thereof include compounds having a pentaerythritol skeleton such as pentaerythritol tri(meth)acrylate and dipentaerythritol penta(meth)acrylate.
[0102] The urethane (meth) acrylate obtained by the reaction of a diisocyanate with a (meth) acrylic compound having one hydroxyl group and two or more (meth) acryloyl groups in one molecule has two urethane bonds and four or more (meth) acryloyl groups in one molecule. The number of (meth) acryloyl groups in the urethane (meth) acrylate may be 6 or more or 8 or more, or 12 or less or 10 or less.
[0103] As the urethane (meth)acrylate, commercially available products such as those produced by Kyoeisha Chemical, Shin-Nakamura Chemical, Negami Industries, Mitsubishi Chemical, Daicel-Allnex, and Resonac can be used.
[0104] From the viewpoint of compatibility with the acrylic base polymer and adjustment of the adhesive force of the adhesive layer, the molecular weight of the urethane (meth) acrylate is preferably 300 to 10,000, more preferably 500 to 2,000, and may be 600 to 1,500 or 700 to 1,200. From the same viewpoint, the functional group equivalent (g / eq) of the (meth) acryloyl group of the urethane (meth) acrylate is preferably 80 to 5,000, more preferably 90 to 1,000, further preferably 100 to 300, and may be 110 to 250 or 120 to 200.
[0105] The content of the photocuring agent in the adhesive composition (the total of the multifunctional (meth)acrylate without a urethane bond and the urethane (meth)acrylate) is preferably 3 parts by weight or more, more preferably 5 parts by weight or more, further preferably 7 parts by weight or more, and may be 8 parts by weight or more or 10 parts by weight or more, relative to 100 parts by weight of the acrylic base polymer. By setting the compounding amount of the photocuring agent to the above range, it is easy to peel off from the adherend before photocuring, and a reinforcement film that can be firmly bonded to the adherend by photocuring can be obtained.
[0106] The more the amount of photocuring agent, the smaller the adhesive force between the adhesive and the adherend before photocuring, and the better the peelability. On the other hand, when the amount of photocuring agent is too much, the photocuring agent is easy to ooze out, and when the reinforcing film is peeled off from the adherend, the exuded component is sometimes transferred to the adherend and becomes the cause of pollution. In addition, when the amount of photocuring agent is too much, there is a tendency that the adhesive after photocuring has low viscosity, insufficient adhesive force and softness. Therefore, relative to 100 parts by weight of the base polymer, the content of the photocuring agent is preferably less than 40 parts by weight, more preferably less than 30 parts by weight, further preferably less than 25 parts by weight, and can also be less than 20 parts by weight or less than 15 parts by weight.
[0107] From the viewpoint of adjusting the adhesion between the pressure-sensitive adhesive layer and the adherend before and after photocuring to an appropriate range, the content of the multifunctional (meth)acrylate having an oxyalkylene chain but not a urethane bond is preferably 3 to 30 parts by weight, more preferably 4 to 25 parts by weight, further preferably 5 to 20 parts by weight, and may also be 6 to 15 parts by weight, 7 to 13 parts by weight, or 8 to 12 parts by weight, relative to 100 parts by weight of the acrylic base polymer.
[0108] From the viewpoint of adjusting the adhesion between the adhesive layer and the adherend before and after photocuring to an appropriate range, the content of the urethane (meth) acrylate is preferably 0.03 to 5 parts by weight, more preferably 0.05 to 4 parts by weight, further preferably 0.08 to 3 parts by weight, and may also be 0.1 to 2.5 parts by weight or 0.15 to 2 parts by weight, relative to 100 parts by weight of the acrylic base polymer.
[0109] Compared with polyfunctional (meth)acrylates without oxyalkylene chains, polyfunctional (meth)acrylates with oxyalkylene chains have lower compatibility with acrylic base polymers. Therefore, polyfunctional (meth)acrylates with oxyalkylene chains tend to be localized on the surface of the adhesive layer (near the bonding interface with the adherend), and tend to form a weak boundary layer (WBL) by the photocuring agent localized on the bonding interface with the adherend.
[0110] If WBL is formed, the liquid properties of the surface (bonding interface) become stronger while maintaining the overall properties of the adhesive layer such as the storage elastic modulus, so there is a tendency for the adhesive force to become smaller. Therefore, the adhesive layer before photocuring is easily peeled off from the adherend. When the adhesive layer with WBL is photocured by making the photocuring agent biased near the bonding interface with the adherend, the curing reaction of the photocuring agent is easy to proceed near the bonding interface where the density of the photocuring agent is high, so the adhesive force is easy to increase. In addition, when WBL is formed, there is a tendency to suppress the increase of the storage elastic modulus, which is a main property, in the adhesive after photocuring.
[0111] By including a carbamate (meth)acrylate as a photocuring agent in addition to a multifunctional (meth)acrylate having an oxyalkylene chain but not having a carbamate bond, there is a tendency for the adhesive force of the adhesive layer before photocuring to become smaller. One reason is believed to be the effect of promoting the formation of WBL caused by the combined use of a carbamate (meth)acrylate and a multifunctional (meth)acrylate not having a carbamate bond, particularly a multifunctional (meth)acrylate having an oxyalkylene chain.
[0112] When the acrylic base polymer contains a nitrogen atom-containing monomer as a monomer component, the initial adhesive force to the adherend subjected to the surface activation treatment tends to be increased, but by containing urethane (meth) acrylate as a photocuring agent, the increase in the initial adhesive force to the adherend subjected to the surface activation treatment tends to be suppressed. This is considered to be because, in addition to the WBL formation promotion effect brought about by urethane (meth) acrylate, the urethane (meth) acrylate present near the bonding interface with the adherend also has the effect of reducing the interaction between the adherend and the acrylic base polymer.
[0113] The adherends that have been subjected to surface activation treatment by plasma treatment or the like contain a large number of active groups such as hydroxyl, carbonyl, and carboxyl groups, and have a strong intermolecular interaction with the nitrogen atoms of the base polymer of the adhesive, so the adhesive strength is easily increased. In particular, when the adherend is a polyimide, polar groups such as amic acid, terminal amino groups, and carboxyl groups (or carboxylic anhydride groups) are activated by the activation treatment, so that the interaction with the nitrogen atoms of the acrylic base polymer is strong, and the initial adhesive strength is easily increased by the activation treatment.
[0114] It is believed that when urethane (meth) acrylate as a photocuring agent is present near the bonding interface with the adherend, NH and CO of the urethane bond are likely to form intermolecular interactions based on hydrogen bonds with polar groups of the adherend, so the interaction between the acrylic base polymer and the adherend is relatively weakened. In the adhesive layer before photocuring, the urethane (meth) acrylate as a photocuring agent is in a liquid state and does not have high cohesive force like the acrylic base polymer containing nitrogen atoms. Therefore, even if the urethane (meth) acrylate forms an intermolecular interaction with the adherend, the adhesive force is hardly increased.
[0115] On the other hand, in the adhesive layer after photocuring, the acrylic base polymer having a cross-linked structure forms a polymer network with the polymer formed by curing of the photocuring agent, so the nitrogen atoms of the acrylic base polymer and the nitrogen atoms of the urethane (meth) acrylate strongly interact with the adherend. Therefore, it is believed that the adhesive layer after photocuring and the adhesion at high temperature to the adherend are improved by the acrylic base polymer containing nitrogen atoms and the urethane (meth) acrylate as the photocuring agent.
[0116] (Photopolymerization Initiator)
[0117] The photopolymerization initiator generates active species by irradiation with active light rays, and promotes the curing reaction of the photocuring agent. As the photopolymerization initiator, a photoradical polymerization initiator (photoradical generator) is preferably used.
[0118] As the photo-radical polymerization initiator, a photo-radical polymerization initiator that generates free radicals by irradiating visible light or ultraviolet light having a wavelength shorter than 450 nm is preferred, and examples thereof include hydroxyketones, benzyl dimethyl ketals, aminoketones, acylphosphine oxides, benzophenones, trichloromethyl-containing triazine derivatives, etc. The photo-polymerization initiator may be used alone or in combination of two or more.
[0119] The content of the photopolymerization initiator in the adhesive layer 2 is preferably 0.01 to 5 parts by weight, more preferably 0.02 to 3 parts by weight, and further preferably 0.03 to 2 parts by weight, relative to 100 parts by weight of the base polymer. The content of the photopolymerization initiator in the adhesive layer 2 is preferably 0.02 to 20 parts by weight, more preferably 0.05 to 10 parts by weight, and further preferably 0.1 to 7 parts by weight, relative to 100 parts by weight of the photocuring agent.
[0120] <Other ingredients>
[0121] As described above, the photocurable adhesive composition constituting the adhesive layer 2 includes an acrylic base polymer, a photocuring agent, and a photopolymerization initiator. The adhesive composition may include components other than these.
[0122] For example, the adhesive composition may contain an oligomer having a lower molecular weight than the base polymer. For example, the adhesive composition may contain an acrylic oligomer having a weight average molecular weight of about 1,000 to 30,000 in addition to the acrylic base polymer.
[0123] In addition to the above-mentioned components, the adhesive composition may also contain additives such as silane coupling agents, tackifiers, crosslinking accelerators, crosslinking retarders, plasticizers, softeners, antioxidants, anti-degradation agents, fillers, colorants, ultraviolet absorbers, surfactants, antistatic agents, etc. within the range that does not impair the characteristics of the present invention.
[0124] As a crosslinking accelerator (crosslinking catalyst), organic metal compounds such as organic metal complexes (chelates), compounds of metals and alkoxy groups, and compounds of metals and acyloxy groups can be listed; as well as tertiary amines, etc. From the perspective of suppressing the crosslinking reaction in a solution state at room temperature and ensuring the shelf life of the adhesive composition, organic metal compounds are preferred. In addition, from the perspective of easily introducing a uniform crosslinked structure as a whole in the thickness direction of the adhesive layer, as a crosslinking accelerator, an organic metal compound that is liquid at room temperature is preferred. As metals of the organic metal compound, iron, tin, aluminum, zirconium, zinc, titanium, lead, cobalt, zinc, etc. can be listed.
[0125] Examples of the crosslinking retarder include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate; β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone; and alcohols such as tert-butyl alcohol.
[0126] [Production of reinforcement film]
[0127] A reinforced film can be obtained by laminating the photocurable adhesive layer 2 on the film substrate 1. The adhesive layer 2 may be directly formed on the film substrate 1, or an adhesive layer formed in a sheet form on another substrate may be transferred to the film substrate 1.
[0128] The above-mentioned adhesive composition is applied to the substrate by roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, curtain coating, lip coating, die coating, etc., and the solvent is dried and removed as needed to form an adhesive layer. As a drying method, an appropriate method can be appropriately adopted. The heating and drying temperature is preferably 40 to 200 ° C, more preferably 50 to 180 ° C, and more preferably 70 to 170 ° C. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and more preferably 10 seconds to 10 minutes.
[0129] When the adhesive composition contains a crosslinking agent, it is preferred to crosslink by heating or aging while or after the solvent is dried. The heating temperature and heating time are appropriately set according to the type of crosslinking agent used, and crosslinking is usually carried out by heating at a range of 20 to 160° C. for 1 minute to 7 days. The heating for drying and removing the solvent can also serve as the heating for crosslinking.
[0130] After the crosslinking structure is introduced into the polymer by the crosslinking agent, the photocuring agent also remains in an unreacted state. Therefore, the adhesive layer 2 is formed of a photocurable adhesive composition containing an acrylic base polymer introduced with a crosslinking structure, a photocuring agent, and a photopolymerization initiator. When the adhesive layer 2 is formed on the film substrate 1, it is preferred to attach a release liner 5 to the adhesive layer 2 for the purpose of protecting the adhesive layer 2. Crosslinking can be performed after attaching the release liner 5 to the adhesive layer 2.
[0131] When the pressure-sensitive adhesive layer 2 is formed on another substrate, the reinforced film is obtained by transferring the pressure-sensitive adhesive layer 2 onto the film substrate 1 after drying the solvent. The substrate used for forming the pressure-sensitive adhesive layer may be used as the release liner 5 as it is.
[0132] As the release liner 5, a plastic film such as polyethylene, polypropylene, polyethylene terephthalate, polyester film, etc. is preferably used. The thickness of the release liner is usually 3 to 200 μm, preferably about 10 to 100 μm. It is preferred that the contact surface of the release liner 5 with the adhesive layer 2 is subjected to a release treatment using a release agent such as a silicon-based, fluorine-based, long-chain alkyl-based or fatty acid amide-based release agent or silica powder. By subjecting the surface of the release liner 5 to a release treatment, when the film substrate 1 and the release liner 5 are peeled off, peeling occurs at the interface between the adhesive layer 2 and the release liner 5, and the state in which the adhesive layer 2 is fixed to the film substrate 1 is maintained. The release liner 5 can be subjected to an antistatic treatment on either or both of the release-treated surface and the non-treated surface. By subjecting the release liner 5 to an antistatic treatment, the charge when the release liner is peeled off from the adhesive layer can be suppressed.
[0133] [Reinforcement film characteristics and use of reinforcement film]
[0134] The reinforcing film of the present invention is used by being attached to a device or a component of the device. The adhesive layer 2 of the reinforcing film 10 is fixed to the film substrate 1, and the adhesive force to the adherend is small before being photocured after being attached to the adherend. Therefore, the reinforcing film is easily peeled off from the adherend before photocuring.
[0135] The adherend to which the reinforcement film is bonded is not particularly limited, and various electronic devices, optical devices and their constituent components can be listed. In one embodiment, the reinforcement film is bonded to the surface of a bendable flexible device. The bendable device has a hinge portion and can be bent with the hinge portion as the center. The bending angle can be set arbitrarily, and it can also be bent (folded) 180°. In the case where the device is a display device, the reinforcement film can be bonded to the surface of the screen side, and the reinforcement film can also be bonded to the back side (housing). In a flexible device that is bendable at a specified position such as a hinge portion, bending and stretching are repeatedly performed at the same position when it is in use.
[0136] The enhancement film can be attached to the entire surface of the adherend, or it can be selectively attached only to the part that needs to be enhanced (enhancement target area). After the enhancement film is attached to the entire part that needs to be enhanced (enhancement target area) and the area that does not need to be enhanced (non-enhancement target area), the enhancement film is cut off and the enhancement film is peeled off from the non-enhancement target area, thereby making a device with the enhancement film attached only to the enhancement target area. If the adhesive is before light curing, the enhancement film is temporarily fixed to the surface of the adherend, and the adhesive force is small, so the enhancement film can be easily peeled off from the surface of the adherend.
[0137] By laminating the reinforcing film, appropriate rigidity can be imparted, so for thin components such as flexible devices, the effects of improved operability and damage prevention can be expected. In the manufacturing process of the device, when the reinforcing film is laminated to the semi-finished product, the reinforcing film can also be laminated to the semi-finished product of a large size before being cut into the product size. The reinforcing film can be laminated in a roll-to-roll manner on the mother roll of the device manufactured by the roll-to-roll process.
[0138] For example, after the reinforcement film is attached to the mother roll of the device or its semi-finished product in a roll-to-roll manner, the mother roll attached with the reinforcement film is cut and separated into individual products, and only the reinforcement film is cut by half cutting, and the reinforcement film in the non-reinforcement target area is peeled off, thereby obtaining a device with the reinforcement film attached to the reinforcement target area. The cutting method is not particularly limited, and an appropriate cutting method such as a rotary cutter, a press-in knife (such as a Thomson knife), a laser cutter, etc. can be used.
[0139] Before laminating the reinforcement film, the surface of the adherend may be activated for the purpose of cleaning, etc. Examples of the surface activation treatment include plasma treatment, corona treatment, glow discharge treatment, etc. As described above, by including carbamate (meth) acrylate as a photocuring agent, even when the acrylic base polymer contains nitrogen atoms, the excessive increase in the initial adhesive force of the adherend whose surface has been activated can be suppressed. The adhesive force F1 between the adherend that has been surface activated and the adhesive layer before photocuring is preferably 1.4 times or less of the adhesive force F0 between the adherend that has not been surface activated and the adhesive layer before photocuring, and can be 1.3 times or less or 1.2 times or less.
[0140] From the viewpoint of easy peeling from the adherend and preventing residual adhesive on the adherend after peeling the reinforcing film, the adhesive force (initial adhesive force) between the adhesive layer 2 and the adherend before photocuring is preferably 0.5N / 25mm or less, more preferably 0.4N / 25mm or less, further preferably 0.3N / 25mm or less, and may also be 0.25N / 25mm or less or 0.2N / 25mm or less. From the viewpoint of preventing peeling of the reinforcing film during storage and handling, the adhesive force between the adhesive layer 2 and the adherend before photocuring is preferably 0.005N / 25mm or more, more preferably 0.01N / 25mm or more.
[0141] The adhesive strength was determined by a peel test using a polyimide film as the adherend, a tensile speed of 300 mm / min, and a peeling angle of 180°. Unless otherwise specified, the adhesive strength is a measured value at 25°C. The adhesive strength between the adhesive layer before photocuring and the adherend was measured using a sample that was left to stand at 25°C for 30 minutes after bonding.
[0142] From the viewpoint of making it easy to peel the reinforcement film from the adherend treated with plasma, the adhesion force F1 of the adhesive layer of the reinforcement film at a temperature of 25°C to the polyimide film treated with plasma before photocuring is preferably in the above range. The adhesion force F0 of the adhesive layer before photocuring to the polyimide film not subjected to surface activation treatment such as plasma treatment at a temperature of 25°C is preferably 0.4N / 25mm or less, more preferably 0.35N / 25mm or less, and further preferably 0.3N / 25mm or less, and may be 0.25N / 25mm or less or 0.2N / 25mm or less. As described above, F1 / F0 is preferably 1.4 or less, and may also be 1.3 or less or 1.2 or less.
[0143] The shear storage elastic modulus (hereinafter referred to as "storage elastic modulus") of the adhesive layer 2 before photocuring at a temperature of 25°C is preferably 15 kPa or more, more preferably 20 kPa or more, and may be 25 kPa or more or 30 kPa or more. The larger the storage elastic modulus of the adhesive layer before photocuring at room temperature, the better the cutting processability, and there is a tendency that the residual adhesive on the adherend is suppressed when the reinforcing film is peeled off from the adherend.
[0144] On the other hand, when the storage elastic modulus of the adhesive layer at room temperature before photocuring is too large, the storage elastic modulus of the adhesive layer after photocuring also tends to increase, and sometimes the adhesion and impact resistance to the adherend are insufficient. In addition, when the storage elastic modulus of the adhesive layer before photocuring is large, the storage elastic modulus of the adhesive layer after photocuring also tends to increase. When applied to foldable devices, the adhesive layer cannot absorb the strain of the bending part and its surroundings, and the reinforcing film is easily peeled off from the device. Therefore, the storage elastic modulus of the adhesive layer before photocuring at a temperature of 25°C is preferably less than 60 kPa, more preferably less than 55 kPa, further preferably less than 50 kPa, and may also be less than 45 kPa or less than 40 kPa.
[0145] The storage elastic modulus of the adhesive layer is obtained by reading the value at a predetermined temperature when measured at a frequency of 1 Hz and a temperature increase rate of 5°C / min in a range of -70 to 200°C according to the method described in JIS K7244-1 "Plastics - Test methods for dynamic mechanical properties". In this specification, the storage elastic modulus is a value at a temperature of 25°C unless otherwise specified.
[0146] After the reinforcing film is attached to the adherend, the adhesive layer 2 is irradiated with active light, thereby photocuring the adhesive layer. As the active light, ultraviolet rays are preferred. The irradiation intensity and irradiation time of the active light can be appropriately set according to the composition, thickness, etc. of the adhesive layer 2. The irradiation of the active light of the adhesive layer 2 can be implemented from any side of the film substrate 1 side and the adherend side, or the irradiation of the active light can be performed from both sides.
[0147] When the adhesive layer 2 is photocured, the photocuring agent undergoes a curing reaction, and the bonding force with the adherend increases. From the perspective of bonding reliability during practical use of the device, the bonding force F2 between the adhesive layer after photocuring and the adherend (polyimide film treated with plasma) at a temperature of 25°C is preferably 3N / 25mm or more, more preferably 5N / 25mm or more, and may also be 7N / 25mm or more, 9N / 25mm or more, or 10N / 25mm or more. The bonding force F2 between the adhesive layer after photocuring and the adherend is preferably 10 times or more of the bonding force F1 between the adhesive layer before photocuring and the adherend, more preferably 15 times or more, further preferably 20 times or more, and may be 30 times or more or 50 times or more.
[0148] The adhesion F3 between the adhesive layer after photocuring and the adherend (polyimide film treated with plasma) at a temperature of 85°C is preferably 1N / 25mm or more, more preferably 2N / 25mm or more, further preferably 3N / 25mm or more, and may be 4N / 25mm or more, 5N / 25mm or more, or 6N / 25mm or more. As described above, the adhesive composition contains an acrylic base polymer having nitrogen atoms and contains urethane (meth) acrylate as a photocuring agent, thereby reducing the initial adhesion to the adherend subjected to the surface activation treatment, and achieving high adhesion in a high temperature environment after photocuring.
[0149] From the viewpoint of achieving high adhesion to the adherend after photocuring, the storage elastic modulus of the adhesive layer after photocuring at a temperature of 25°C is preferably 40 kPa or more, more preferably 50 kPa or more, and may also be 55 kPa or more or 60 kPa or more. On the other hand, when the storage elastic modulus of the adhesive layer after photocuring is too large, there is a tendency for the adhesion and impact mitigation (cushioning) to the adherend to be reduced. In addition, when the storage elastic modulus of the adhesive layer after photocuring is too large, when applied to a foldable device, the reinforcing film is easily peeled off from the device at the bending portion and its periphery. Therefore, the storage elastic modulus of the adhesive layer after photocuring at a temperature of 25°C is preferably 150 kPa or less, more preferably 120 kPa or less, further preferably 100 kPa or less, and may also be 90 kPa or less or 80 kPa or less.
[0150] There is a tendency that the storage elastic modulus of the adhesive layer after photocuring becomes smaller as the amount of the crosslinking agent and the amount of the photocuring agent is smaller, and there is a tendency that the increase in the storage elastic modulus of the adhesive layer caused by photocuring becomes smaller as the amount of the photocuring agent is smaller. In addition, by including a multifunctional (meth)acrylate having an oxyalkylene chain and a carbamate (meth)acrylate without a carbamate bond as a photocuring agent, there is a tendency to suppress the increase in the storage elastic modulus of the adhesive layer caused by photocuring and to improve the bonding strength to the adherend.
[0151] By laminating the reinforcing film, appropriate rigidity is imparted to the adherend, and stress is relieved and dispersed, thereby suppressing various troubles that may occur in the manufacturing process, improving production efficiency and yield.
[0152] The adhesive layer 2 of the reinforcement film of the present invention is photocurable, and the curing time can be set arbitrarily. Before the adhesive layer is photocured, the reinforcement film of the present invention has a low adhesive force to the adherend after surface treatment, so it is easy to peel off from the adherend, and even in the case of lamination or poor lamination, reprocessing is also easy. In addition, processing such as selectively removing the reinforcement film from the non-reinforcement target area is also easy.
[0153] After the adhesive layer is photocured, it exhibits high adhesive strength to the adherend, and has high adhesive strength even at high temperatures, so the reinforcement film is not easily peeled off from the device surface. In a device with a reinforcement film in which the reinforcement film of the present invention is attached to a flexible device using a resin substrate, the reinforcement film is not easily peeled off at the bent portion even when bent repeatedly, and the bonding reliability is excellent.
[0154] [Example]
[0155] The present invention will be further described below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples.
[0156] [Preparation of base polymer]
[0157] <Polymer A>
[0158] In a reaction vessel equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen inlet pipe, 20 parts by weight of butyl acrylate (BA), 70 parts by weight of 2-ethylhexyl acrylate (2EHA), 8 parts by weight of lauryl acrylate (LA), 1 part by weight of 4-hydroxybutyl acrylate (4HBA) and 1 part by weight of N-vinyl-2-pyrrolidone (NVP) as monomers, 0.1 parts by weight of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, and 233 parts by weight of ethyl acetate as a solvent were added, and nitrogen was introduced and nitrogen replacement was performed for about 1 hour while stirring. Then, the mixture was heated to 60°C and reacted for 7 hours to obtain a solution of acrylic polymer A with a weight average molecular weight of 1.8 million.
[0159] <Polymer B>
[0160] A solution of an acrylic polymer B having a weight average molecular weight of 550,000 was obtained in the same manner as in the polymerization of the polymer A except that the amount of the thermal polymerization initiator (AIBN) was changed to 0.2 parts by weight.
[0161] <Polymers C to E>
[0162] The amount of monomers charged was changed as shown in Table 1. Solutions of polymers C to E were obtained in the same manner as in the polymerization of polymers A and B. 0.2 parts by weight of thermal polymerization initiator was used in the polymerization of polymers C and D, and 0.1 parts by weight of thermal polymerization initiator was used in the polymerization of polymer E.
[0163] The monomer ratios charged in acrylic polymers A to E and the weight average molecular weight (Mw) of the polymers are listed in Table 1. The weight average molecular weight (polystyrene equivalent) was measured using GPC ("HLC-8220GPC" manufactured by Tosoh Corporation) under the following conditions.
[0164] Sample concentration: 0.2 wt% (tetrahydrofuran solution).
[0165] Sample injection volume: 10 μL.
[0166] Eluent: THF (tetrahydrofuran).
[0167] Flow rate: 0.6 mL / min.
[0168] Measurement temperature: 40℃.
[0169] Sample column: TSKguardcolumn SuperHZ-H (1 column) + TSKgel SuperHZM-H (2 columns).
[0170] Reference column: TSKgel SuperH-RC (1 column).
[0171] In Table 1, monomers are described by the following abbreviations.
[0172] BA: Butyl acrylate.
[0173] 2EHA: 2-ethylhexyl acrylate.
[0174] NOAA: n-octyl acrylate.
[0175] MMA: methyl methacrylate.
[0176] LA: Lauryl acrylate.
[0177] 2HEA: 2-Hydroxyethyl acrylate.
[0178] 4HBA: 4-Hydroxybutyl acrylate.
[0179] NVP: N-vinyl-2-pyrrolidone.
[0180] [Table 1]
[0181]
[0182] [Production of reinforcement film]
[0183] <Preparation of Adhesive Composition>
[0184] A crosslinking agent, a multifunctional acrylate (having no urethane bond) and a urethane acrylate as a photocuring agent, and a photopolymerization initiator were added to the acrylic polymer solution and uniformly mixed to prepare an adhesive composition shown in Table 2.
[0185] As a crosslinking agent, an isocyanurate of hexamethylene diisocyanate ("CORONATE HX" manufactured by Tosoh) was added in the amount shown in Table 2. As a photopolymerization initiator, 0.3 parts by weight of "Omnirad 651" manufactured by IGM Resins was added relative to 100 parts by weight of the solid content of the acrylic polymer. Photocuring agents (multifunctional acrylates and urethane acrylates) were added in the amounts shown in Table 2. The addition amounts in Table 2 are amounts relative to 100 parts by weight of the acrylic polymer (parts by weight of the solid content). Details of the photocuring agents are as follows.
[0186] (Multifunctional acrylate)
[0187] A200: "NK ester A200" manufactured by Shin-Nakamura Chemical Industry Co., Ltd. (polyethylene glycol #200 (n=4) diacrylate; molecular weight 308, functional group equivalent 154 g / eq).
[0188] M350: trimethylolpropane EO-modified (n=1) triacrylate ("ARONIX M-350" manufactured by Toagosei Co., Ltd., functional group equivalent: 143 g / eq).
[0189] ADPHE: ethoxylated dipentaerythritol polyacrylate ("NK ester A-DPH-12E" manufactured by Shin-Nakamura Chemical Industry Co., Ltd., functional group equivalent weight: about 200 g / eq).
[0190] TMPT: trimethylolpropane triacrylate ("NK Ester A-TMPT" manufactured by Shin-Nakamura Chemical Industry Co., Ltd., functional group equivalent weight 99 g / eq).
[0191] (Urethane Acrylate)
[0192] UA306: Pentaerythritol triacrylate-toluene diisocyanate adduct ("UA-306T" manufactured by Kyoeisha Chemical, functional group equivalent: 128 g / eq).
[0193] UA510: dipentaerythritol pentaacrylate hexamethylene diisocyanate adduct ("UA-510H" manufactured by Kyoeisha Chemical, functional group equivalent: 181 g / eq).
[0194] UF-X9-83: Urethane acrylate having a polycarbonate skeleton ("UF-X9-83" manufactured by Kyoeisha Chemical, number of functional groups: 2 to 3, weight average molecular weight: 8400).
[0195] <Application and cross-linking of adhesive solution>
[0196] The adhesive composition was applied to a 50 μm thick polyethylene terephthalate film substrate ("DIAFOILT100" manufactured by Mitsubishi Chemical) without surface treatment using a fountain roll to a thickness of 15 μm after drying. After drying at 130°C for 1 minute to remove the solvent, the release-treated surface of a release liner (a 25 μm thick polyethylene terephthalate film with a silicone release treatment on the surface) was attached to the applied surface of the adhesive. Then, an aging treatment was performed for 4 days in an atmosphere of 25°C, and cross-linking was performed to obtain a reinforced film having an adhesive sheet laminated on the film substrate and a release liner temporarily fixed thereon.
[0197] [evaluate]
[0198] <Adhesion to polyimide film>
[0199] (Adhesive Strength of Adhesive Layer Before Photocuring)
[0200] A 25 μm thick polyimide film (UBE "UPILEX25S") was attached to a glass plate via a double-sided adhesive tape (Nitto Denko "No.531") to obtain a polyimide film substrate for measurement. The release liner was peeled off from the surface of a reinforcement film cut into a size of 25 mm wide x 100 mm long and attached to the polyimide film substrate for measurement using a hand roller.
[0201] After the sample was allowed to stand at 25°C for 30 minutes, the edge of the film substrate of the reinforcement film was held with a chuck and a 180° peel test was performed at a tensile speed of 300 mm / min to measure the peel strength (adhesion F0 of the reinforcement film to the non-plasma treated polyimide film).
[0202] While conveying the polyimide film substrate for measurement at a conveying speed of 3 m / min, the surface of the polyimide film was subjected to plasma treatment using a normal pressure plasma treatment machine under the condition of an electrode voltage of 160 V. A reinforcing film was laminated to the polyimide film after the plasma treatment using a hand roller, and the adhesive force F1 to the polyimide film after the plasma treatment was measured by a 180° peel test in the same manner as described above.
[0203] Based on the obtained results, the ratio F1 / F0 of the adhesive force F1 after the plasma treatment to the adhesive force F0 without the plasma treatment was calculated.
[0204] (Adhesion strength of adhesive layer after photocuring)
[0205] After bonding the reinforcement film to the polyimide film substrate for measurement (after plasma treatment), the film was irradiated from the reinforcement film side (film substrate side) using an LED light source with a wavelength of 365 nm to a cumulative light intensity of 4000 mJ / cm 2 The adhesive layer was photocured by ultraviolet light. The test sample was used to measure the adhesive force F2 based on the 180° peel test at a temperature of 25°C in the same manner as above. Furthermore, the test sample after the adhesive layer was photocured was stored in an oven at a temperature of 85°C for 5 minutes, and then a 180° peel test was performed in an environment at a temperature of 85°C to measure the adhesive force F3.
[0206] <Storage elastic modulus>
[0207] On the release liner, the adhesive composition was coated and cross-linked in the same manner as above to prepare an adhesive sheet (before photocuring). A release liner was attached to the surface of the adhesive layer of the adhesive sheet before photocuring, oxygen was blocked, and irradiated with a 365nm LED lamp at 4000mJ / cm 2 The adhesive sheet before and after photocuring were laminated to prepare a measurement sample with a thickness of about 1.5 mm. The dynamic viscoelasticity was measured using a rotational rheometer ("Discovery-HR2" manufactured by TA Instruments) under the following conditions, and the shear storage elastic modulus G' value at 25°C was read.
[0208] (Measurement conditions)
[0209] Deformation mode: twist.
[0210] Measuring frequency: 1Hz.
[0211] Heating rate: 5°C / min.
[0212] Measuring temperature: -70~200℃.
[0213] Shape: parallel plate 8.0mmφ.
[0214] <Adherent contamination>
[0215] The release liner was peeled off from the surface of the reinforcement film cut into 25 mm wide x 100 mm long, and the film was attached to the polyimide film substrate for measurement (not treated with plasma) using a hand roller. After standing at 25°C for 30 minutes or 24 hours, the reinforcement film was peeled off from the polyimide film, and the surface of the polyimide film was visually observed under a fluorescent lamp to confirm whether there was contamination. The contamination of the adherend was evaluated according to the following criteria.
[0216] A: No contamination was observed in the sample peeled off after being left to stand for 24 hours.
[0217] B: Contamination was observed in the sample peeled off after standing for 24 hours, but no contamination was observed in the sample peeled off after standing for 30 minutes.
[0218] C: Contamination was observed in the sample peeled off after being left to stand for 30 minutes.
[0219] Table 2 shows the composition of the binder of each reinforcement film (the type of base polymer, the amount of crosslinking agent added, the type and amount of photocuring agent added) and the evaluation results.
[0220] [Table 2]
[0221]
[0222] In Comparative Example 1, which used an adhesive composition in which 10 parts by weight of a multifunctional acrylate (M350) was blended as a photocuring agent relative to 100 parts by weight of polymer A, the adhesive force F0 to the polyimide film that was not subjected to plasma treatment exceeded 0.5 N / 25 mm, showing a large initial adhesive force. In addition, in Comparative Example 1, the adhesive force F1 to the polyimide film that was subjected to plasma treatment increased to more than 1.5 times the adhesive force F0 to the polyimide film that was not subjected to plasma treatment, and the initial adhesive force was greatly increased by plasma treatment of the adherend.
[0223] In Example 1, in which 0.15 parts by weight of urethane acrylate (UA306) was blended as a photocuring agent in addition to 10 parts by weight of multifunctional acrylate (M350), the adhesive force F0 to the polyimide film not subjected to plasma treatment was less than 1 / 3 of that in Comparative Example 1. In Example 1, the adhesive force F1 to the polyimide film subjected to plasma treatment was 1.2 times the adhesive force F0 to the polyimide film not subjected to plasma treatment, and the increase in the initial adhesive force of the adherend caused by the plasma treatment was suppressed.
[0224] In Example 1, the adhesive strength is greatly increased by photocuring the adhesive, and has a high adhesive strength of more than 6N / 25mm even at a high temperature of 85°C. In addition, the storage elastic modulus of the adhesive after photocuring is less than 70kPa, and in addition to the high adhesive strength, it also has flexibility suitable for foldable devices and the like.
[0225] In Example 16, which uses a polymer B having a molecular weight lower than that of polymer A as the base polymer of the adhesive, the initial adhesive force is low regardless of the presence or absence of plasma treatment of the adherend, and the adhesive exhibits high adhesive force to the adherend after photocuring, as in Example 1. In Example 16, the storage elastic modulus of the adhesive after photocuring is smaller than that of Example 1, and the flexibility is excellent. On the other hand, the adhesive force F3 at high temperature of the adhesive after photocuring in Example 16 exhibits a smaller value than that in Example 1.
[0226] The initial adhesive strength of Comparative Example 5, which used polymer C containing no monomer component containing nitrogen atoms as the base polymer of the adhesive, and Comparative Example 7, which used polymer E, was small, and the increase in the initial adhesive strength of the adherend caused by plasma treatment was suppressed. However, the adhesive strength F3 of the photocured adhesives of Comparative Examples 5 and 7 at high temperature was less than 1N / 25mm, and the bonding reliability was poor.
[0227] From the comparison between Examples 1 and 16 and Comparative Examples 5 and 7, it can be seen that the reinforced film having a photocurable adhesive layer comprising an acrylic polymer containing a nitrogen atom, a multifunctional (meth)acrylate without a urethane bond, and a multifunctional (meth)acrylate with a urethane bond shows a small initial adhesion force even to an activated adherend, and shows a high adhesion force to the adherend after the adhesive is photocured, and also has a high adhesion force at high temperature, and has excellent bonding reliability.
[0228] Comparative Example 6, which used polymer D containing 15 parts by weight of a monomer component (NVP) having a nitrogen atom as the base polymer of the adhesive, had a high initial adhesive force, and the adhesive force to the adherend treated with plasma increased by more than 1.4 times. From this result, it can be seen that even when urethane (meth) acrylate is used as a photocuring agent, it is difficult to reduce the initial adhesive force when the nitrogen atom content of the acrylic base polymer is high.
[0229] In Examples 2 to 4, in which the amount of urethane acrylate (UA306) added was increased compared to Example 1, the initial adhesive force to the adherend was small, the increase in the initial adhesive force of the adherend caused by the plasma treatment was suppressed, and the adhesive force of the adhesive layer after photocuring at high temperature was also excellent. By comparing Examples 1 to 4, the following tendency was observed: the larger the amount of urethane acrylate added, the smaller the initial adhesive force, and the higher the adhesive force of the adhesive layer after photocuring at high temperature.
[0230] In Example 12 and Example 13, which used urethane acrylates different from Example 1, the initial adhesive force was small, the increase in the initial adhesive force due to the plasma treatment was suppressed, and the adhesive force of the adhesive layer after photocuring was also excellent at a high temperature. These results show that urethane acrylate contributes to the reduction of the initial adhesive force and the increase of the adhesive force of the adhesive layer after photocuring at a high temperature.
[0231] In Examples 3 and 4, in which the amount of urethane acrylate was increased, the initial adhesive force was lower and the peeling property was improved compared with Examples 1 and 2, but contamination of the adherend was observed when the reinforcing film was peeled off before the photocuring of the adhesive. It is believed that the excessive photocuring agent seeped out on the surface of the adhesive layer and transferred to the adherend, which caused the contamination.
[0232] Compared with Example 1 using a 6-functional urethane acrylate (UA306), Example 12 using a 10-functional urethane acrylate (UA510) has a smaller initial adhesive force and a larger adhesive force at high temperature after photocuring. On the other hand, Example 13 using a high molecular weight urethane acrylate (UF-X9-83) has a larger initial adhesive force and a smaller adhesive force at high temperature than Example 1 and Example 10. From these results, it can be seen that the more functional groups of the urethane acrylate and the smaller the functional group equivalent, the greater the effect of reducing the initial adhesive force and improving the adhesive force at high temperature.
[0233] Examples 14 and 15, in which the type of multifunctional acrylate without a carbamate bond is changed, are similar to Example 1 in that the initial adhesive force to the adherend is small, the increase in the initial adhesive force of the adherend caused by plasma treatment is suppressed, and the adhesive force of the adhesive layer after photocuring at high temperature is also excellent. On the other hand, in Comparative Example 4 using TMPT as a multifunctional acrylate without an oxyalkylene chain, the initial adhesive force is high, and even if the adhesive is photocured, the adhesive force hardly increases. From these results, it can be seen that by using carbamate (meth) acrylate and a multifunctional (meth) acrylate with an oxyalkylene chain as a photocuring agent, it is possible to take into account both the reduction of the initial adhesive force and the improvement of the adhesive force at high temperature.
[0234] In Comparative Example 2, in which the amount of the multifunctional acrylate (M350) having an oxyalkylene chain was 2 parts by weight, the initial adhesive force was high, but the adhesive force at a high temperature after photocuring was insufficient. When comparing Examples 1, 8, and 9 in which the amount of the multifunctional (meth)acrylate was changed, the following tendency was observed: the larger the amount of the multifunctional acrylate, the smaller the initial adhesive force, and the larger the adhesive force at a high temperature after photocuring.
[0235] On the other hand, in Examples 10 and 11, in which the amount of multifunctional acrylate was further increased compared to Example 1, as the amount of multifunctional acrylate increased, although the initial adhesive force decreased, a tendency was observed that the adhesive force after photocuring also decreased. In addition, in Examples 10 and 11, the storage elastic modulus of the adhesive layer after photocuring was larger than that of Example 1, and contamination of the adherend was observed when the reinforcing film was peeled off before photocuring of the adhesive. In Comparative Example 3, in which the amount of multifunctional acrylate was further increased, the adhesive force of the adhesive after photocuring was as low as less than 1N / 25mm, and the storage elastic modulus exceeded 150kPa.
[0236] These results show that increasing the amount of photocuring agent tends to reduce the initial adhesive force and increase the adhesive force after photocuring. However, when the amount of photocuring agent is too large, the adhesive after photocuring becomes hard and loses its tackiness, so that high adhesive force cannot be achieved.
[0237] Comparing Example 1 with Examples 5 to 7, the following tendency was observed: as the amount of the crosslinking agent increased, the adhesive force of the pressure-sensitive adhesive layer before and after photocuring decreased, and the storage elastic modulus increased.
[0238] From the above results, it can be seen that the reinforced film having a photocurable adhesive layer comprising an acrylic polymer containing a nitrogen atom, a multifunctional (meth)acrylate without a urethane bond, and a multifunctional (meth)acrylate with a urethane bond shows a small initial adhesion force even to an activated adherend, and shows a high adhesion force to the adherend after the adhesive is photocured, and has a high adhesion force at high temperature and excellent bonding reliability.
Claims
1. A reinforcement film comprising a film substrate and an adhesive layer fixedly laminated on one main surface of the film substrate, wherein: The adhesive layer is formed of a photocurable composition, wherein the photocurable composition includes an acrylic base polymer, a photocuring agent having two or more photopolymerizable functional groups, and a photopolymerization initiator. The acrylic base polymer contains one or more monomers selected from the group consisting of hydroxyl group-containing monomers and carboxyl group-containing monomers and a nitrogen atom-containing monomer as monomer components, A cross-linked structure is introduced into the acrylic base polymer. The content of the nitrogen atom-containing monomer is 0.3 to 10 parts by weight relative to 100 parts by weight of the total monomer components of the acrylic base polymer. The photocurable composition includes 3 to 30 parts by weight of a multifunctional (meth)acrylate having an oxyalkylene chain but not having a urethane bond as the photocuring agent based on 100 parts by weight of the acrylic base polymer, and 0.03 to 5 parts by weight of a urethane (meth)acrylate as the photocuring agent based on 100 parts by weight of the acrylic base polymer.
2. The enhanced film according to claim 1, wherein: The acrylic base polymer has a crosslinked structure introduced therein using 0.05 to 1.0 parts by weight of a crosslinking agent based on 100 parts by weight of the polymer.
3. The enhanced film according to claim 2, wherein: The crosslinking agent is an isocyanate crosslinking agent or an epoxy crosslinking agent.
4. The enhanced film according to claim 1, wherein: The functional group equivalent of the (meth)acryloyl group of the multifunctional (meth)acrylate is 80 to 500 g / eq.
5. The enhanced film according to claim 1, wherein The functional group equivalent of the (meth)acryloyl group of the urethane (meth)acrylate is 80 to 5000 g / eq.
6. The enhanced film according to claim 1, wherein The urethane (meth)acrylate has four or more (meth)acryloyl groups in one molecule.
7. The reinforced film according to any one of claims 1 to 6, wherein The adhesive layer has an adhesive force F0 of 0.4 N / 25 mm or less to the polyimide film at a temperature of 25° C. before photocuring, and an adhesive force F1 of 1.4 times or less to the polyimide film treated with plasma at a temperature of 25° C., The adhesive force F2 of the adhesive layer to the plasma-treated polyimide film at a temperature of 25°C after photocuring is greater than 3.0 N / 25 mm, and the adhesive force F3 of the adhesive layer to the plasma-treated polyimide film at a temperature of 85°C after photocuring is greater than 1.0 N / 25 mm.
8. The reinforced film according to any one of claims 1 to 6, wherein The adhesive layer has a shear storage elastic modulus of 150 kPa or less at a temperature of 25° C. after photocuring.
9. A method for manufacturing a device, which is a method for manufacturing a device having a reinforcement film attached to the surface, wherein: After temporarily fixing the adhesive layer of the reinforcement film according to any one of claims 1 to 8 to the surface of an adherend, The adhesive layer is irradiated with active light rays to photo-cure the adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.
10. The method for manufacturing a device according to claim 9, wherein: After the reinforcement film is temporarily fixed to the adherend, before the adhesive layer is photocured, the reinforcement film temporarily fixed to the adherend is cut to peel and remove the reinforcement film from a partial region on the adherend.
11. The method for manufacturing a device according to claim 9 or 10, wherein: Before temporarily fixing the reinforcement film, the surface activation treatment of the adherend is performed.
12. The method for manufacturing a device according to claim 11, wherein: The surface activation treatment is plasma treatment.
13. The method for manufacturing a device according to claim 9 or 10, wherein: The adherend includes a polyimide film, and the adhesive layer of the reinforcement film is bonded to the polyimide film.
14. The method for manufacturing a device according to claim 9 or 10, wherein: The adherend is a bendable image display element.
15. A reinforcement method, which is a reinforcement method of laminating a reinforcement film on the surface of an adherend, wherein: The adhesive layer of the reinforcement film according to any one of claims 1 to 8 is temporarily fixed to the surface of the adherend, The adhesive layer is irradiated with active light rays to photo-cure the adhesive layer, thereby increasing the adhesive strength between the reinforcing film and the adherend.
Citation Information
Patent Citations
Reinforcement film, manufacturing method of device, and reinforcement method
JP2020132846A